2017
DOI: 10.1103/physrevb.95.155422
|View full text |Cite
|
Sign up to set email alerts
|

Lifshitz interaction can promote ice growth at water-silica interfaces

Abstract: At air-water interfaces, the Lifshitz interaction by itself does not promote ice growth. On the contrary, we find that the Lifshitz force promotes the growth of an ice film, up to 1-8 nm thickness, near silica-water interfaces at the triple point of water. This is achieved in a system where the combined effect of the retardation and the zero frequency mode influences the short-range interactions at low temperatures, contrary to common understanding. Cancellation between the positive and negative contributions … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(52 citation statements)
references
References 55 publications
3
46
3
Order By: Relevance
“…In contrast to their results, we have found that buoyancy combined with dispersion and double layer forces establish an equilibrium where large ice particles float on the surface while small (micron-sized) ice particles are trapped at a distance below a water surface [45]. Further, it was shown that ice formation can be induced by dispersion forces near silica-water interfaces (where silica can be used as a model for rock material) [34]. For CO 2 gas hydrates and the N 2 gas hydrate, energy minimum exist corresponding in each case to an equilibrium ice film thickness: d CO2 =44, 43 and 37 Å for CO 2 volume fractions p = 5.75, 6 and 7.67, respectively, and d N2 =32 Å.…”
Section: Gas Hydrate Specific Ice Formationcontrasting
confidence: 82%
See 2 more Smart Citations
“…In contrast to their results, we have found that buoyancy combined with dispersion and double layer forces establish an equilibrium where large ice particles float on the surface while small (micron-sized) ice particles are trapped at a distance below a water surface [45]. Further, it was shown that ice formation can be induced by dispersion forces near silica-water interfaces (where silica can be used as a model for rock material) [34]. For CO 2 gas hydrates and the N 2 gas hydrate, energy minimum exist corresponding in each case to an equilibrium ice film thickness: d CO2 =44, 43 and 37 Å for CO 2 volume fractions p = 5.75, 6 and 7.67, respectively, and d N2 =32 Å.…”
Section: Gas Hydrate Specific Ice Formationcontrasting
confidence: 82%
“…These dielectric functions are for a system at the triple point of water, close to zero degrees Celsius at low pressure. The final results for ice melting [19,20,21,22,23,31,32] and water freezing [33,34] are sensitive to the dielectric functions of ice and water since these are extremely similar when the water is in equilibrium with the ice. We show in Fig.…”
Section: Materials Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…As an application of the results found here, that ice grows inside water at the triple point of water, we would like to investigate the relevance of this effect to the predictions for liquid water on distant planets and their moons. In presence of a silica surface we have predicted that ice can form in water based on Lifshitz theory [17]. Boström et al further proposed that Lifshitz forces could lead to ice formation on some specific gas hydrate surfaces in water [39].…”
Section: Discussionmentioning
confidence: 99%
“…This expression leads to d 1 ≈ 0.41 µm and d 2 ≈ 7.83nm, which are in the right ballpark of 0.37 µm and 3.56nm, respectively. We have been unable to find a more accurate analytical estimate, because we are dealing with a discrete function of the Matsubara mode numbers n, in addition to the fact that the zero mode behaves significantly differently from other modes [17].…”
Section: Lifshitz Energy For Planar Geometrymentioning
confidence: 99%